The dream thieves - Stiefvater, Maggie, 1981- (2014)
Now that the ley lines around Cabeswater are awake, magic is swirling around Blue and The Raven boys and Ronan Lynch's ability to pull objects from his dreams is almost out of control but worst of all, the mysterious Gray Man is stalking the Lynch family, looking for something called the Greywaren.
Originally published: New York : Scholastic Press, 2013.
Keywords: Magic -- Juvenile fiction; Dreams -- Juvenile fiction; Family secrets -- Juvenile fiction; Fiction; Young adult fiction